The advantage of the platelet-to-lymphocyte ratio over neutrophil-to-lymphocyte ratio as novel markers of erythropoietin resistance in hemodialysis patients - Golubović, Sonja; Knežević, Violeta; Azaševac, Tijana; Ćelić, Dejan (Vojnosanitetski pregled, 2023)
Background/Aim. Inflammation is one of the common factors that contribute to erythropoiesis stimulating agents (ESA) treatment resistance in hemodialysis patients. Lately, it is assessed by using new markers of inflammation, which are platelet-to-lymphocyte ratio (PLR) and neutrophil-to-lymphocyte ratio (NLR). Their association with this therapy has not been fully investigated. The aim of the study was to evaluate the relationship between PLR, NLR, and ESA hyporesponsiveness index (EHRI). Methods. The research was conducted as a cross-sectional study and included 90 hemodialysis patients, who underwent clinical and laboratory testing in the form of physical examination and biochemical analyses. In all patients, the EHRI calculation was performed. Results. It is shown that EHRI had a statistically significant positive correlation with PLR (p
Keywords: blood platelets; erythropoietin; inflammation; lymphocytes; neutrophils; renal dialysis